2015
DOI: 10.1242/jeb.120956
|View full text |Cite
|
Sign up to set email alerts
|

Interactive effects of early and later nutritional conditions on the adult antioxidant defence system in zebra finches

Abstract: In vertebrates, antioxidant defences comprise a mixture of endogenously produced components and exogenously obtained antioxidants that are derived mostly from the diet. It has been suggested that early-life micronutritional conditions might influence the way in which the antioxidant defence system operates, which could enable individuals to adjust the activity of the endogenous and exogenous components in line with their expected intake of dietary antioxidants if the future environment resembles the past. We i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 57 publications
(59 reference statements)
2
25
0
Order By: Relevance
“…[22,44]), our results are consistent with it. We are aware of a single study providing some support to the environmental matching hypothesis in terms of oxidative stress [45]. Zebra finches enduring similar accessibility to dietary micronutrients (mostly antioxidant vitamins) during both growth and sexual maturity had better enzymatic (erythrocyte glutathione peroxidase) and non-enzymatic (similar to PLAOX) antioxidant defences than those experiencing upward or downward changes in micronutrient availability.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…[22,44]), our results are consistent with it. We are aware of a single study providing some support to the environmental matching hypothesis in terms of oxidative stress [45]. Zebra finches enduring similar accessibility to dietary micronutrients (mostly antioxidant vitamins) during both growth and sexual maturity had better enzymatic (erythrocyte glutathione peroxidase) and non-enzymatic (similar to PLAOX) antioxidant defences than those experiencing upward or downward changes in micronutrient availability.…”
Section: Discussionmentioning
confidence: 89%
“…Zebra finches enduring similar accessibility to dietary micronutrients (mostly antioxidant vitamins) during both growth and sexual maturity had better enzymatic (erythrocyte glutathione peroxidase) and non-enzymatic (similar to PLAOX) antioxidant defences than those experiencing upward or downward changes in micronutrient availability. Nonetheless, the impact of reproduction in this context was untested [45].…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this prediction, both pre-and postnatal stress experience has been related to variability in adult redox status (Constantini et al, 2012;Marasco et al, 2013;Noguera et al, 2015;Romero-Haro and Alonso-Alvarez, 2015;Zimmer and Spencer, 2015). For instance, following an intense heat stress in adulthood, zebra finches (Taeniopygi guttata) that had been exposed to a mild heat stress as juveniles acquired less oxidative damage than individuals with no prior exposure to heat stress (Constantini et al, 2012).…”
Section: Introductionmentioning
confidence: 80%
“…Similarly, plasticity of oxidative stress resistance and antioxidant defenses has also been observed following prenatal glucocorticoid exposure (Marasco et al, 2013;Zimmer and Spencer, 2015) and limited posthatch nutrient availability (Noguera et al, 2015;Romero-Haro and Alonso-Alvarez, 2015). The apparent priming of redox systems by early life experiences has been suggested to arise through epigenetic modifications of gene expression or post-translational alterations of enzymes (Romero-Haro and Alonso-Alvarez, 2015;Noguera et al, 2015) and may result in context-dependent fitness consequences (Marasco et al, 2013;Constantini et al, 2014;Noguera et al, 2015;Zimmer and Spencer, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, the composition of the diet in early life in terms of antioxidant content may play an important role, since it can influence the way in which the antioxidant defence system operates later in life (Blount et al, 2003a; Noguera, Monaghan & Metcalfe, 2015; Romero-Haro & Alonso-Alvarez, 2015; Romero-Haro, Sorci & Alonso-Alvarez, 2016). For example, it has recently been shown that when diet composition in terms of antioxidant vitamins and mineral content is slightly lower than normal, young zebra finch ( Taeniopygia guttata ) nestlings can adjust the development of their antioxidant defence system (i.e., by increasing the production of some endogenous antioxidants and/or the absorption of exogenous vitamins) and compensate for such deficiencies (Noguera, Monaghan & Metcalfe, 2015). However, although potentially beneficial in the short term, theory predicts that these early phenotypic adjustments may be detrimental if (nutritional) conditions change later during development (reviewed by Nettle & Bateson, 2015).…”
Section: Introductionmentioning
confidence: 99%